KUALITAS VISUM ET REPERTUM PERLUKAAN DI RUMAH SAKIT UMUM DAERAH DUMAI PERIODE 1 JANUARI 2008 - 31 DESEMBER 2012 - Ridho Maulana; Dedi Afandi; Fifia Chandra (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
About 50%-70% of case that come to a hospital especially to theemergency room are physical trauma or injuries cases. The quality of VeR servicedirectly reflect medicolegal services in hospital because it has broad impactjuridical and can determine one’s fate. This research were done to find out thequality of VeR of injury in Dumai General Hospital during 1 January 2008-31December 2012. This is a descriptive retrospective research. It used Herkutantosscoring method. The sample was all of population were the VeR data in DumaiGeneral Hospital during 1 January 2008-31 December 2012 that were completeand has been signed by the doctor who did the examination. It had been gotten166 VeR reports in Dumai General Hospital during 1 January 2008-31 December2012. Injury survivors most cases are in the age group <18 years old as many as55 victims (33,1%). The overview of the living victims were most frequent malewas 131 victims (78,9%) and the most frequent violence that were experienced bythe victims were blunt violence was 154 VeR (92,8%) with the highest age group<18 years old. About 90% showed good quality in preliminary unit of VeR,44,15% showed poor quality in reporting unit and about 26,65% also showedpoor quality in inference unit. It can be concluded that quality of VeR reports inDumai General Hospital during 1 January 2008-31 December 2012 was 37,46%which was mean it was poor quality.Keywords: Visum et Repertum, injury, the quality of Visum et Repertum of injury